Time and money : the macroeconomics of capital structure - Garrison, Roger W. (Foundations of the market economy series., 2001)
Time and Money argues persuasively that the troubles which characterise modern capital-intensive economies, particularly the episodes of boom and bust, may best be analysed with the aid of a capital-based macroeconomics.